Density temporal variation and ecological aspects of ichthyoplankton in the epipelagic zone of the Cariaco Trench, Venezuela - Rondón-Ramos, Mariana (2023)
The composition and ecological aspects of fish larvae present in the Cariaco Trench, Venezuela, were described. Planktonic samples were collected between October 2012 and December 2013 during seven campaigns. A standard conical hanging net with a 35 cm mouth diameter and a 300-micron pore was used. Drafts were made horizontally, at a depth of 20 meters, with a duration of 15 minutes, at a speed of 2 knots. A total of 322 fish larvae was obtained: in 16 orders, 20 families and 28 species. The families Carangidae and Gobiidae presented the highest number of species, with 6 and 3, respectively; while Bregmacerotidae was the one that contributed with the highest density of organisms (53.29 org/100 m3), being the species with the highest relative abundance Bregmaceros cantori with 29.81%. In general, monthly diversity was low, with values between 0 and 1.55 bits/ind, not differing statistically between months (KW = 7.604; P = 0.2686). Species richness between 0 and 2.06 did not present differences between months either (KW = 7.0927; P = 0.3124). The ichthyoplankton of the Cariaco Trench was dominated mainly by families of mesopelagic fish such as Bregmacerotidae and Myctophidae. Of the 28 species identified, 54% are of commercial interest to the country, which provides additional value to the Cariaco Trench.